The Use of Peer Support on Adolescent Health Among Senior High School Students - Elly Dwi Wahyuni; Junengsih Junengsih; Erma Yuliani (SEAJOM: The Southeast Asia Journal of Midwifery, 2019)
Background: Problems related to adolescent reproductive behavior are often rooted in a lack of information, understanding and awareness to achieve reproductive health, so that impacts such as risky sexual behavior in adolescents can arise; therefore, the use of peer supports is very important. Objective: to describe the utilization of peer support of the adolescents in SMA Suluh of South Jakarta in 2019. Method: the research type was descriptive quantitative with crosssectional design. The population was all students in one senior high school with a sample of 100 respondents collected through stratified random sampling. Result: This study showed that most of the students had used peer support (66%), and small part of the respondents did not yet utilize peer support (34%). Most of the respondents who did peer support were teenage girls (72%), living with their parent (68%), having good knowledge (66%), school support (70.3%), and support from health workers (67.8%). Conclusion: Most of the respondents had implemented peer support with support system from self-capacity, family support and support from the school